Erlotinib Associated Trichomegaly in a Patient with Chronic Latanoprost Use - CK, Burris; NQ, Richards; CL Jr, Cowan (Journal of Hematology and Oncology Research, 2015)
Trichomegaly is a known adverse effect with the epidermal growth factor receptor inhibitor (EGFRI) and prostaglandin analogue drug classes. We present a chronic Latanoprost user who developed symptomatic trichomegaly subsequent to initiating an EGFRI medication and believe this case offers evidence that the two classes of medications may cause a similar eyelash manifestation through different mechanisms.
Keywords: Trichomegaly; Erlotinib; Latanoprost; Epidermal Growth Factor Receptor Inhibitor; Prostaglandin Analogue; Eyelash